Imaging the Margins: Representation and Identity in Visual Art Reflections - Biglari Afshar, Fatemeh (Curtin University, 2019)
This thesis (creative exegesis) examines the research and creative processes that went into making several bodies of visual artwork during the author’s doctoral candidature. Broadly, the research and creative works presented are all concerned with issues of representation affecting non-Western subjects—particularly women from Islamic cultural backgrounds—and the visual coding of identity or cultural difference in the works of such artists.